EL VERBO DIVINO COMO IMAGEN, EXPRESIÓN Y REVELACIÓN EN SAN BUENAVENTURA. - María León-Sanz, Isabel (Revista Española de Filosofía Medieval, 2025)
This study raises some questions that arise from the connection between image and verbum mentis (or idea). It observes how the expressive and revelatory dimensions that are characteristic of both realities are articulated in St. Bonaventure’s thought; and it considers the implications that derive in relation to Jesus Christ, Image of God the Father and Incarnate Word. First of all, it introduces how these issues were posed in the intellectual tradition received by Bonaventura. Next, the main features of the Bonaventurian conception of the image are presented. Then it is shown how the image is related to the verbum mentis in this author, through concepts such as likeness, generation, expression and manifestation. Finally, some consequences of considering these ideas in the eternal and incarnate Word are pointed out.